Music as the language of the unconscious: listening, sublimation, and subjectivity in psychoanalytic practice (Interapia – Journal of Clinic, Culture and Mental Sciences, 2025)
ABSTRACTThe article explores music as a language of the unconscious and its relevance in psychoanalytic practice, based on Freud, Jung, Lacan, Winnicott, Anzieu, and contemporary authors. The author examines how unconscious contents manifest and become symbolizable through musical creation and listening. Drawing from popular, religious, and instrumental works, the study presents music as a symbolic device for sublimation, affect elaboration, and subjective integration. The paper highlights the aesthetic power of music as a psychoanalytic tool and as a privileged space for meaning-making and emotional transformation.
Keywords: Music; Unconscious; Psychoanalysis; Sublimation; Subjectivity